2020
DOI: 10.1002/anie.202008350
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition of Water, Alcohols, and Amines in Palladium Catalysis

Abstract: The homolytic cleavage of O−H and N−H or weak C−H bonds is a key elementary step in redox catalysis, but is thought to be unfeasible for palladium. In stark contrast, reported here is the room temperature and reversible oxidative addition of water, isopropanol, hexafluoroisopropanol, phenol, and aniline to a palladium(0) complex with a cyclic (alkyl)(amino)carbene (CAAC) and a labile pyridino ligand, as is also the case in popular N‐heterocyclic carbene (NHC) palladium(II) precatalysts. The oxidative addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…Interestingly, a relaxed potential energy surface scan for consecutively shortening the distance of O(1) and H(1) atoms from IN6 offered evidence of the noninnocent ligand behavior of CAAC, in which the carbene carbon (C(1)) acts as an H-shuttle. 53,54 This offered an indication of a carbene-assisted H migration, which leads to polarity reversal of the hydride. Indeed, H(1) can undergo a facile migration to C(1) via TS4 (−101.1 kcal mol −1 ), and this process thus gives rise to an umpolung of the H(1) atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a relaxed potential energy surface scan for consecutively shortening the distance of O(1) and H(1) atoms from IN6 offered evidence of the noninnocent ligand behavior of CAAC, in which the carbene carbon (C(1)) acts as an H-shuttle. 53,54 This offered an indication of a carbene-assisted H migration, which leads to polarity reversal of the hydride. Indeed, H(1) can undergo a facile migration to C(1) via TS4 (−101.1 kcal mol −1 ), and this process thus gives rise to an umpolung of the H(1) atom.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to locate a transition state that corresponds to an O(1)–H(1) bond formation from IN6 were unsuccessful, presumably because of the unmatched charge distribution between the H(1) (−0.18 au) and O(1) (−0.99 au) atoms, indicated by natural population analysis. Interestingly, a relaxed potential energy surface scan for consecutively shortening the distance of O(1) and H(1) atoms from IN6 offered evidence of the noninnocent ligand behavior of CAAC, in which the carbene carbon (C(1)) acts as an H-shuttle. , This offered an indication of a carbene-assisted H migration, which leads to polarity reversal of the hydride. Indeed, H(1) can undergo a facile migration to C(1) via TS4 (−101.1 kcal mol –1 ), and this process thus gives rise to an umpolung of the H(1) atom.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that higher steric bulk in cAACs, than in NHCs and phosphine, also increases the catalytic activity of cAACs complexes, owing to sp 3 ‐hybridization of the α‐carbon [15] . According to the report by Grunwald et al., cAAC stabilized palladium complexes can undergo oxidative addition with water, alcohols, and amines and can be a useful catalyst for O−H and N−H bond activation [32] . Gold(I)‐complexes bearing cAACs as ligands are probably the most thoroughly studied complexes with a broad range of applications in catalysis.…”
Section: Areas Of Caac Chemistrymentioning
confidence: 99%
“… [15] According to the report by Grunwald et al., cAAC stabilized palladium complexes can undergo oxidative addition with water, alcohols, and amines and can be a useful catalyst for O−H and N−H bond activation. [32] Gold(I)‐complexes bearing cAACs as ligands are probably the most thoroughly studied complexes with a broad range of applications in catalysis. In 2007, Bertrand's group demonstrated that cationic cAACs−Au (I) complexes can promote the coupling of terminal alkynes with enamines to produce allenes, [33] while with other catalysts this coupling gives propargyl amines ( A2 ).…”
Section: Areas Of Caac Chemistrymentioning
confidence: 99%